Family planning in carriers of BRCA1 and BRCA2 pathogenic variants. Issue 6 (27th April 2021) - Haddad, Jessica M.; Robison, Katina; Beffa, Lindsey; Laprise, Jessica; ScaliaWilbur, Jennifer; Raker, Christina A.; Clark, Melissa A.; Hofstatter, Erin; Dalela, Disha; Brown, Amy; Bradford, Leslie; Toland, Maris; et al.
Abstract: BRCA1 and BRCA2 pathogenic variant carriers have a high lifetime risk of developing breast and ovarian malignancies. Given the risks and significant ramifications of undergoing risk‐reducing surgeries, many pathogenic variant carriers unaffected by cancer (previvors) struggle with family planning and reproductive decision making. The objective of this study was to determine the attitudes and practices of BRCA1 and BRCA2 pathogenic variant carriers with respect to family planning decision making. A cross‐sectional survey was conducted of BRCA1 and BRCA2 previvors at four Northeastern medical centers. The survey was administered electronically via email using REDCap. The survey included demographic information as well as questions about genetic testing, prophylactic surgeries, family planning, and partnering. Data were analyzed with Fisher's exact tests and t tests. The survey was completed by 139 of 422 BRCA1 and BRCA2 pathogenic variant carriers (response rate 33%). Thirteen were excluded from analysis due to self‐reported cancer history. Of the remaining 126, 21 (16.7%) were male and 105 (83.3%) were female. Female participants <35 years old at the time of genetic testing were significantly more likely than those 35 or greater to report feeling urgency to have a family after finding out about their BRCA1 and BRCA2 pathogenic variant ( p < 0.0001). Younger women also reported their genetic status had a stronger impact on their romantic relationships ( p = 0.029). Men were significantly more likely to report that they felt no urgency to have a family compared to women ( p < 0.0001). Our study reflects the complex decision making for previvors and the intricacies of family planning in this population. Providers can use this knowledge as a guide to counsel patients about reproductive options.